The Cheng Hoon Teng Temple / Faeiz Ahmad - Ahmad, Faeiz (Faculty of Architecture, Planning and Surveying, 1972)
Malacca was the original capital of an ancient Malay Kingdom. In a time before Columbus Discovered America, a Ming Emperor's envoy had organised China's first trade arrangement with Malacca. Following that visit trade grew throughout the country. The Chinese while doing trade, brought along their culture, custom and art to this peninsula. That easily influence is seen in many existing old temples and landsmark. The oldest Chinese Temple in Malaysia - Cheng Hoon Teng Temple is a typical example.